Support for improved quality control but misplaced criticism of GBR science. Reply to viewpoint "The need for a formalised system of Quality Control for environmental policy-science" by P. Larcombe and P. Ridd (Marine Pollution Bulletin 126: 449–461, 2018). Issue 1 (April 2018) - Schaffelke, Britta; Fabricius, Katharina; Kroon, Frederieke; Brodie, Jon; De'ath, Glenn; Shaw, Roger; Tarte, Diane; Warne, Michael; Thorburn, Peter
Abstract: This is a response to the published Viewpoint by Larcombe and Ridd (2018). We agree with Larcombe and Ridd (2018) that scientific merit goes hand in hand with rigorous quality control. However, we are responding here to several points raised by Larcombe and Ridd (2018) which in our view were misrepresented. We describe the formal and effective science review, synthesis and advice processes that are in place for science supporting decision-making in the Great Barrier Reef. We also respond in detail to critiques of selected publications that were used by Larcombe and Ridd (2018) as a case study to illustrate shortcomings in science quality control. We provide evidence that their representation of the published research and arguments to support the statement that "many (…) conclusions are demonstrably incorrect" is based on misinterpretation, selective use of data and over-simplification, and also ignores formal responses to previously published critiques.